Comprehensive Review of Healthcare Workforce Challenges, Technological Solutions, And Training Programs - Alqarni, Abdullah Saleh Abdullah; Alwadai, Saad Eisa Ali; Al qarni, Ali Saleh Mohmmed; Jazza, Saqer Abdullah Saeed; Alshehri, Riyadh Abdullah Mohammed; Alqahtani, Ibtisam Saeed; Al thabit, Mohammed Abdullah; Saif, Salem Abdullah Sales; Alahmari, Khalid Abdullah; Alshehri, Ali Gharim Fadel (Journal of Ecohumanism, 2024)
The healthcare workforce is under pressure from, among other things, workforce deficit, staff fatigue, and changes in demand for skills due to the changing technological environment. This review, therefore, reviews these workforce challenges and examines how AI, telemedicine technology, EHRs, and wearable technology can suggest some of the mentioned workforce pressures. Moreover, it evaluates the changing trends in healthcare training programs and explores the need to adopt new technologies for innovation. Healthcare organizations can take advantage of the right technological solutions and increase the medical staff’s and patients’ effectiveness through increased efficiency, education, and training. Based on the arguments made throughout this paper, the following suggestions are made for healthcare organizations, policymakers, and educators to prepare the workforce for future needs.